2012
DOI: 10.1038/nature11377
|View full text |Cite
|
Sign up to set email alerts
|

Afternoon rain more likely over drier soils

Abstract: (2012), Afternoon rain more likely over drier soils, Nature, 489(7416), 423-426 (10.1038/nature11377) Land surface properties influence the partition of radiative energy between latent and sensible heat fluxes during daytime. A climatically important process during dry periods is the impact of soil water deficit on limiting evapotranspiration, leading to increased surface heating of the lower atmosphere 1-2 . Soil moisture can influence the development of convective storms through modification of low level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
540
5
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 539 publications
(571 citation statements)
references
References 41 publications
25
540
5
1
Order By: Relevance
“…A satellite observational study of soil moisture and precipitation in some regions showed that a drier surface induces stronger precipitation particularly over the relatively drier land-surface conditions (Taylor et al 2012). However, additional studies are needed to determine if their results are in accordance with those in the tropical Asian monsoon regions where the land-surface conditions are relatively wet.…”
Section: Possible Mechanism Underlying the Weakening Of Ri Over Landmentioning
confidence: 67%
“…A satellite observational study of soil moisture and precipitation in some regions showed that a drier surface induces stronger precipitation particularly over the relatively drier land-surface conditions (Taylor et al 2012). However, additional studies are needed to determine if their results are in accordance with those in the tropical Asian monsoon regions where the land-surface conditions are relatively wet.…”
Section: Possible Mechanism Underlying the Weakening Of Ri Over Landmentioning
confidence: 67%
“…Our results here indicate that the convective schemes used in GCMs might also be part of the reason. Berg et al [2013] also attributed the difference of TFS results and those in other studies showing negative feedbacks [e.g., Carleton et al, 2008;Wang et al, 2009;Taylor et al, 2011Taylor et al, , 2012 to the coupling indices framework and the spatial scale difference. The positive feedback as shown through TFS in our coarse spatial resolution simulations ($2.88 here) is not necessarily contradictory with those studies that emphasize scales of coupling in the 10-100 km range accounting for surface heterogeneity, which are not included in our framework.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 87%
“…Counterintuitive effects of explicit entrainment can also introduce exotic behaviors [Hohenegger et al, 2009]. Thus, both positive and negative soil moisture feedback on precipitation can occur as shown in many studies [Hohenegger et al, 2009;Findell et al, 2011;Taylor et al, 2011Taylor et al, , 2012Gentine et al, 2013c;Guillod et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies (e.g., Taylor et al, 2012) showed that in the Sahel region, thunderstorms occur preferably over regions drier than their surroundings. In other areas of the world the synoptic forcing is usually so strong that a robust relationship of causality between soil moisture and precipitation cannot be found (Tuttle and Salvucci, 2017).…”
Section: Introductionmentioning
confidence: 99%